Analysis of microbial diversity of traditional Chinese starters and screening of special flavor yeast for Chinese baked flatbread - Yang, Yixi; Wang, Yuanhui; Li, Boyu; Chen, Chen; Zhao, Yixian; Pan, Lulu; Tocmo, Restituto; Zhang, Guoqiang; Zhang, Qidong; Zhang, Huang; Sun, Juntao (Frontiers in Nutrition, 2026)
IntroductionTraditional Chinese starters have unclear microbial complexity and community functions.MethodsTo screen functional yeasts for flavor enhancement of Chinese baked flatbread (CBF), Saccharomyces cerevisiae Y4 was isolated and identified from traditional Chinese starters using a combined approach of high-throughput sequencing and culturomics. The traditional starters samples were aseptically collected from Luohe, Xinxiang in Henan province and Rizhao in Shandong province.ResultsThe analysis of microbial communities revealed that Luohe starter had the highest fungal (Chao1 = 271.86) and bacterial (Chao1 = 341.76) richness, with dominant genera including Saccharomyces and Lactiplantibacillus. Saccharomyces cerevisiae Y4 showed the following performance: saturated gas production at 48 h, 12% ethanol tolerance, high acid tolerance (OD value below 0.15), and 1975 mL gas production in fermented dough. CBF fermented by Y4 had a high sensory score (82.8) and 40 volatiles, including the unique 1-octen-3-ol and a prominent level of phenethyl acetate content.DiscussionIn this study, a superior yeast strain was identified, providing theoretical insights and valuable microbial resources for optimizing the flavor of CBF.